Community Study of Brachyuran Crab at Setiu Lagoon, Terengganu, Malaysia - MOHAMAD TAUFEK ZAKIRAH; ZAKARIA NURUL- ZALIZAHANA; NURULAFIFAH YAHYA; AHMAD SYAFIQ AHMAD NASIR; ZAINUDIN BACHOK (Borneo Journal of Resource Science and Technology, 2022)
Brachyuran crab of Setiu Lagoon was systematically sampled between July 2011 and May 2012 to determine the community structure of animals and their relationship with environmental parameters. The semiterrestrial crabs were collected from a 100 m2 quadrat at eight stations. In addition, fishing devices were used to collect true aquatic crabs employed at the subtidal habitat. Forty-four species and 13 families were identified representing semiterrestrial and true aquatic crabs (i.e., Sesarmidae, Varunidae, Grapsidae, Ocypodidae, Macropthalmidae, Dotillidae, Camptandriidae, Pilumnidae, Portunidae, Eriphiidae, Oziidae, Dorippidae and Leucosiidae). Parasesarma plicatum, Perisesarma eumolpe, Clistocoeloma merguiense, Haberma sp., Uca (Austruca) annulipes, Uca (Gelasimus) vocans, and Moguai aloutos) were widely distributed in this lagoon. ST5 (at mix mangrove forest) recorded the highest number of species with density (12 ind.m-2), species richness (D = 2.68 ± 0.72), species evenness; (J’ = 0.90 ± 0.06) and species diversity (H’ = 2.17 ± 0.32) as compared to other stations. The results indicated that water salinity, pH and sediment grain size influence the community pattern of brachyuran in this lagoon.